2023
DOI: 10.1186/s12981-023-00507-1
|View full text |Cite
|
Sign up to set email alerts
|

An indirect comparison of 144-week efficacy, safety, and tolerability of dolutegravir plus lamivudine and second-generation integrase inhibitor–based, 3-drug, single-tablet regimens in therapy-naive people with HIV-1

Abstract: Background The long-term efficacy and safety of the 2-drug regimen dolutegravir (DTG) + lamivudine (3TC) and 3-drug single-tablet regimens recommended for antiretroviral therapy (ART)-naive people with HIV-1 (PWH) have yet to be compared directly in clinical trials. This indirect treatment comparison (ITC) was conducted to compare the durability of efficacy and long-term safety of DTG + 3TC vs second-generation, integrase strand transfer inhibitor (INSTI)-based, 3-drug, single-tablet regimens b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Results of an indirect treatment comparison have indicated that DTG + 3TC offered similar efficacy with fewer serious adverse events (AEs) than B/F/TAF and dolutegravir/abacavir/lamivudine at week 144 after ART initiation. [10] This finding reflected no observed differences between 3TC + DTG and B/F/TAF in long-term efficacy among treatment naïve PWH. Nevertheless, it is still unknown whether B/F/TAF has a different impact on initial HIV-1 RNA decay kinetics compared to DTG + 3TC in real-life contexts.…”
Section: Introductionmentioning
confidence: 77%
“…Results of an indirect treatment comparison have indicated that DTG + 3TC offered similar efficacy with fewer serious adverse events (AEs) than B/F/TAF and dolutegravir/abacavir/lamivudine at week 144 after ART initiation. [10] This finding reflected no observed differences between 3TC + DTG and B/F/TAF in long-term efficacy among treatment naïve PWH. Nevertheless, it is still unknown whether B/F/TAF has a different impact on initial HIV-1 RNA decay kinetics compared to DTG + 3TC in real-life contexts.…”
Section: Introductionmentioning
confidence: 77%